SOME FIXED POINT RESULTS IN THE GENERALIZED CONVEX METRIC SPACES - Dogan, Kadri; Gursoy, Faik; Karakaya, Vatan (TURKIC WORLD MATHEMATICAL SOC, 2020)
In this study, we introduce a new three step iteration process and show that the iteration process converges to the unique fixed point by two theorems under different conditions of contractive mappings on the generalized G- convex metric spaces. Also, we investigate data dependence result for this iterative process in the generalized G- convex metric spaces.
Keywords: Convex G-metric spaces; G-convergence; Fixed point iteration process; ITERATION; Mathematics